PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNINGTERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA BERBANTU APLIKASI PhETMTs MUHAMMADIDYAH 17 PUNGGULANKELAS VII - Amanda Rizky Aulia Putri; Muthia Dewi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
The study aims to determine whether Guided Discovery Learning influences students' mathematical problem-solving ability assisted by the PhET application at VIIth-grade students of MTs Muhammadiyah 17 Punggulan. This study used a quantitative method with a Quasi-Experimental method using a Two-Group Pretest-Posttest Design. In addition, this study found that the sample used was normally distributed and homogeneous. The results of data analysis indicate that the instrument used was valid and reliable. The population in this study are VIIth-grade students of MTs Muhammadiyah 17 Punggulan, with a sample consisting of two classes: VIIth- 1 grade as the experimental class and VIIth- 2 grade as the control class. The instrument used was a posttest of mathematical problem solving ability using a t-test with a significance level of 0.05. The results of the t-test obtained tcount = 2.716> ttable = 2.004 so that H0 was rejected and H1 was accepted, so it can be concluded that there is an influence of the Discovery Learning learning model assisted by the PhET application on students' mathematical problem solving abilities on the material of flat shapes at VIIth grade studentas of  MTs Muhammadiyah 17 Punggulan in 2025/2026 Academic Year.